Psychological Literacy Weakly Differentiates Students by Discipline and Year of Enrolment - Heritage, Brody; Roberts, Lynne D.; Gasson, Natalie (Frontiers in Psychology, 2016)
Psychological literacy, a construct developed to reflect the types of skills graduates of a psychology degree should possess and be capable of demonstrating, has recently been scrutinised in terms of its measurement adequacy. The recent development of a multi-item measure encompassing the facets of psychological literacy has provided the potential for improved validity in measuring the construct. We investigated the known-groups validity of this multi-item measure of psychological literacy to examine whether psychological literacy could predict a) students’ course of enrolment and b) students’ year of enrolment. 515 undergraduate psychology students, 87 psychology / human resource management students, and 83 speech pathology students provided data. In the first year cohort, the Reflective Processes factor significantly predicted psychology and psychology / human resource management course enrolment, although no facets significantly differentiated between psychology and speech pathology enrolment. Within the second year cohort, Generic Graduate Attributes and Reflective Processes differentiated psychology and speech pathology course enrolment. Generic Graduate Attributes differentiated first-year and second-year psychology students, with second-year students more likely to have higher scores on this factor. Due to weak support for known-groups validity, further measurement refinements are recommended to improve the construct’s utility.